The Impact of YouTube Digital Storytelling on Students’ English Retelling Skills - Rabi'ah Al-Adawiyah; Dzul Rachman; Ade Ismail Ramadhan Hamid (Borneo Educational Journal (Borju), 2025)
This study investigates the impact of YouTube-based digital storytelling on students' English retelling skills in an EFL context. The research was motivated by students' common struggles with vocabulary retention, speaking fluency, and confidence when retelling stories in English. Utilizing a mixed-method approach, the study involved 55 students from the English Education Program at Universitas Muhammadiyah Kalimantan Timur. Data were collected through a Likert-scale questionnaire and semi-structured interviews. Quantitative data were analyzed using SPSS to obtain mean scores and descriptive statistics, while qualitative data were examined using thematic analysis. The findings revealed that digital storytelling significantly improved students' vocabulary, fluency, and confidence. Interview responses supported these results, highlighting how visual and audio elements in YouTube storytelling helped students recall new words, understand narrative structure, and express ideas with greater ease. The study concludes that YouTube digital storytelling is an effective, engaging, and accessible tool for enhancing retelling skills in EFL learners. The originality of this study lies in its focus on integrating multimodal digital input with narrative learning, offering pedagogical insights into low-resource and tech-friendly learning strategies for speaking development.